Faktor-Faktor yang Berhubungan dengan Konsumsi Sayur dan Buah pada Siswa Sekolah Dasar - Mindo Lupiana; Sadiman Sadiman (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2017)
Indonesian people's fruit consumption is still relatively low compared to other countries that do not have the resources to produce fruits. Purpose: this study was to determine the factors associated with fruit and vegetable consumption in elementary school students. Methods: This research method uses a cross sectional design. The research population was all students in class V totaling 123 students and the study sample was 100 students who were determined using simple random sampling. This research was conducted in Negeri 1 Rajabasa Raya Bandar Lampung City. Data processing in this study was univariate and bivariate using the chi square test. Results: The results showed that the factors associated with fruit and vegetable consumption were preference (p = 0.001), knowledge (p = 0,000) and attitude (p = 000). The unrelated variable is the availability at home (p = 0.813). Conclusion: Factors that increase consumption of fruit and vegetables in elementary school students are preference, good knowledge, and supportive attitude. Socialization needs to be done to increase knowledge about the benefits and effects of less consumption of fruit and vegetables, put up a poster media about the benefits and effects of less consumption of fruits and vegetables.